Combined toxicity characteristics and regulation of residual quinolone antibiotics in water environment. (January 2021) - Ren, Zhixing; Xu, Haihong; Wang, Yingwei; Li, Yufei; Han, Song; Ren, Jinbo
Abstract: In this study, the mixture toxicity index method was used to evaluate the combined toxicity of residual Quinolones (QNs) on algae in twelve groups of water environment reported in the literature. The selected three sets of data (II, Ⅺ, and Ⅻ) combined with full factorial design method were used to analyze the significance of the combined toxicity. Subsequently, molecular docking was used to reveal the significant mechanism of the primary effect of the combined toxicity. Finally, based on the sensitivity analysis method, the acid-base conditions affecting the combined toxicity were screened, and molecular dynamics simulation was used to control the combined toxicity in the water environment. The results of the mixture toxicity index method showed that the combined toxicity in all the twelve groups of water environments was synergistic. The full factorial design method revealed that ciprofloxacin, norfloxacin, enrofloxacin, lomefloxacin, and their binary combinations from the combined toxicity system of QNs, were the significant factors that caused the synergistic toxicity of QNS on algae. Molecular docking confirmed that the total number of amino acids, the number of significant amino acids, and hydrogen bonds of QNs toxic targets were significantly related to the synergistic effect of the combined toxicity. In addition, the molecular dynamics simulation showed that the binding energy of residual QNs and toxic targets changes with the acid-base conditions of the water environment. Thus, the combined toxicity can be slowed down or reduced by adequately adjusting the acid-base condition of the water. Graphical abstract: Image 1 Highlights: Combined toxicity of Quinolones (QNs) on algae of water environment was evaluated. The significance of the combined toxicity of Quinolones (QNs) on algae was analyzed. The significant mechanism of the primary effect of the combined toxicity was reveal. A method of control the combined toxicity of Quinolones (QNs) on algae was obtained.